2023
DOI: 10.1007/s12161-023-02473-w
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Chemical Changes of Coffee Beans During Roasting Using Real-time NIR Spectroscopy and Chemometrics

Abstract: Variations occurring in coffee beans during roasting are ascribable to several chemical-physical phenomena: to quickly track the whole process and to ensure its reproducibility, a process analytical technology (PAT) approach is needed.In this study, a method combining in-line Fourier transform near-infrared (FT-NIR) spectroscopy and chemometric modelling was investigated to get real-time and practical knowledge about the roasting effects on coffee’s chemical-physical composition. In-line spectra were acquired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…There are different types of controlled fermentation used by producers in which yeasts are used to degrade the coffee mucilage without affecting the quality of the bean. However, the pH of coffee is also influenced by factors such as the coffee variety and the geographical location of production [42]. The measurement of • Brix is an indication of the concentration of soluble solids; most of these soluble solids are sucrose.…”
Section: Discussionmentioning
confidence: 99%
“…There are different types of controlled fermentation used by producers in which yeasts are used to degrade the coffee mucilage without affecting the quality of the bean. However, the pH of coffee is also influenced by factors such as the coffee variety and the geographical location of production [42]. The measurement of • Brix is an indication of the concentration of soluble solids; most of these soluble solids are sucrose.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, assuming that the data obtained from the laboratory is represented as model Q, the spectral information obtained from whole leaf scanning is denoted as X, the spectral information obtained from leaf fragment scanning is denoted as Z, and the tobacco chemical composition values measured using continuous flow method are denoted as Y. Based on partial least squares (PLS) modeling, we obtain the model equation ( 2), and then we can calculate the parameters of the model equation (1) using equation (3). Equation ( 1) represents the predictive model we need.…”
Section: Migration Methodsmentioning
confidence: 99%
“…This method only requires obtaining the near-infrared spectral data of the sample, offering fast detection, high timeliness, and non-destructive testing of the sample. Currently, NIR analysis technology has been applied in numerous fields, including agriculture, petrochemicals, pharmaceuticals, food, and clinical settings [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated growing interest in the application of NIR coupled with chemometrics for analyzing coffee samples, encompassing areas such as geographical origin discrimination [ 9 , 17 , 18 ], quality classification [ 19 ], monitoring chemical changes during roasting [ 20 ], predicting stable isotopes and trace elements [ 21 ], and predicting sensory cupping scores [ 15 , 22 ]. While NIR spectra have been employed to predict roast degrees both online and inline, no studies have incorporated initial data from GC-MS to gain additional insights into the volatile composition of different roast degrees, with the ultimate goal of roast degree discrimination.…”
Section: Introductionmentioning
confidence: 99%